2015
DOI: 10.1371/journal.pone.0132808
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Right Ventricular Function Predicts Long-Term Cardiac Re-Hospitalization after Cardiac Surgery

Abstract: BackgroundThe significance of right ventricular ejection fraction (RVEF), independent of left ventricular ejection fraction (LVEF), following isolated coronary artery bypass grafting (CABG) and valve procedures remains unknown. The aim of this study is to examine the significance of abnormal RVEF by cardiac magnetic resonance (CMR), independent of LVEF in predicting outcomes of patients undergoing isolated CABG and valve surgery.MethodsFrom 2007 to 2009, 109 consecutive patients (mean age, 66 years; 38% female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
(40 reference statements)
2
14
0
2
Order By: Relevance
“…Regarding prevalence of RV dysfunction pre-operatively, we found that a large number of patients had RV dysfunction at time of surgery (38%). This prevalence is similar to that reported in the literature: for example, Lella et al showed that CMR-evidenced RV dysfunction occurred in 44% (48/109) among patients undergoing elective CABG and valve surgery [19]. Similarly, Haddad et al demonstrated echo-evidenced RV dysfunction to occur in 22% (11/50) patients undergoing aortic or mitral valve surgery [17].…”
Section: Discussionsupporting
confidence: 83%
“…Regarding prevalence of RV dysfunction pre-operatively, we found that a large number of patients had RV dysfunction at time of surgery (38%). This prevalence is similar to that reported in the literature: for example, Lella et al showed that CMR-evidenced RV dysfunction occurred in 44% (48/109) among patients undergoing elective CABG and valve surgery [19]. Similarly, Haddad et al demonstrated echo-evidenced RV dysfunction to occur in 22% (11/50) patients undergoing aortic or mitral valve surgery [17].…”
Section: Discussionsupporting
confidence: 83%
“…Patients undergoing major vascular surgery are at high risk for postoperative cardiac complications and perioperative morbidity and mortality. 14 In addition to the elevated surgical risk associated with major vascular procedures, the increased perioperative morbidity and mortality has been attributed to a higher prevalence of cardiac disease in the vascular patient population. 5 For example, congestive heart failure (CHF) is an important predictor for postoperative cardiac events in patients undergoing vascular surgery.…”
mentioning
confidence: 99%
“…In addition to LV function improvement, right ventricular (RV) function also improves after CABG, especially in patients with low baseline RV ejection fraction 45 . Preoperative RV systolic dysfunction predicts long-term cardiac re-hospitalization and cardiovascular death 46,47 . Preoperative left atrial enlargement (left atrial diameter ≥ 4 cm) is a strong independent predictor of mortality after CABG 48 .…”
Section: Discussionmentioning
confidence: 99%